2022
DOI: 10.1002/tie.22303
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between home and host institutions on CBA ownership decision

Abstract: Cross-border acquisitions (CBAs) are one of the key strategies for internationalization.However, most of what is known about CBA strategies relies on the effects of the host country's environment or the home country's conditions. In this article, we analyze the interplay between these two important factors. We show that companies from less institutionally developed countries are more influenced by poor institutional conditions found in host countries. We analyzed a dataset of 1,390 cross-border acquisitions pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 102 publications
0
1
0
Order By: Relevance
“…Through factor analysis, we extracted a single-factor score with varimax rotation, which is used in the literature; e.g. (Krug and Falaster, 2023). All factor loadings (range: 0.607 to 0.937) exceed the cutoff (≥ 0.40).…”
Section: Resultsmentioning
confidence: 99%
“…Through factor analysis, we extracted a single-factor score with varimax rotation, which is used in the literature; e.g. (Krug and Falaster, 2023). All factor loadings (range: 0.607 to 0.937) exceed the cutoff (≥ 0.40).…”
Section: Resultsmentioning
confidence: 99%
“…However, Reddy et al (2023) suggested an opposite dynamic where increased ownership is an outcome of home institutional quality enhancement that drives EMFs to seek deeper learning from CBMA targets. Underdeveloped home institutions also affect EMFs' risk preference in ownership sought, such that Latin American acquirers are less negatively affected by host country risk in their ownership, given their adaptability to home high-risk environments (Krug and Falaster, 2023). Despite EMFs' strong CBMA motivation and risk preference, they frequently fail in completing CBMAs because of poor home institutional quality, which undermines their image and competitiveness (He and Zhang, 2018;Zhang, 2022;Zhang et al, 2017).…”
Section: Home Country Factors In Cbmas Bymentioning
confidence: 99%